Population, Poverty, and Sustainable Development : A Review of the Evidence - Das Gupta, Monica (2012)
There is a very large but scattered literature debating the economic implications of high fertility. This paper reviews the literature on three themes: (a) Does high fertility affect low-income countries' prospects for economic growth and poverty reduction? (b) Does population growth exacerbate pressure on natural resources? and (c) Are family planning programs effective at lowering fertility, and should they be publicly funded? The literature shows broad consensus that while policy and institutional settings are key in shaping the prospects of economic growth and poverty reduction, the rate of population growth also matters. Recent studies find that low dependency ratios (as fertility declines) create an opportunity for increasing productivity, savings and investment in future growth. They find that lower fertility is associated with better child health and schooling, and better health and greater labor-force participation for women. They also indicate that rapid population growth can constrain economic growth, especially in low-income countries with poor policy environments. Population growth also exacerbates pressure on environmental common property resources. Studies highlight the deep challenges to aligning divergent interests for managing these resources. However, part of the pressure on these resources can be mitigated by reducing the rate of population growth. Although family planning programs are only one policy lever to help reduce fertility, studies find them effective. Such programs might help especially in the Sub-Saharan African region, where high fertility and institutional constraints on economic growth combine to slow rises in living standards.